POLITICAL POWER AND PARTICIPATION: THE CONTRIBUTIONS OF THE TEXAS COALITION OF BLACK DEMOCRATS - Thompson, John Edward; Rodriguez, Maria Christina (Ayden International Journal of Law, Political Science, and Administration, 2024)
This study investigates the Texas Coalition of Black Democrats' efforts in promoting political participation among diverse Texas Democrats. Informed by the concepts of civic engagement and Black political attitudes, the coalition conducted a survey to capture participants' responses on key issues affecting Black Texans. The survey highlights the coalition's commitment to empowering its members with knowledge about justice, race, equity, healthcare, economic growth, and the importance of political engagement.